Bentuk Tindak Direktif pada Kalimat Deklaratif dalam Serial Drama Jepang - Desy Irmayanti; Isnin Ainie (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2022)
This study discusses the form of directive utterence in Japanese declarative sentences of Japanese drama series entitled Sapuri and Osen. Directive utterence has a purpose to produce an effect in the form of actions taken by the speech partner. The form of directive utterence in declarative sentences has been analyzed using Yasushi’s Theory. This research uses qualitative method and directive utterances in declarative sentence as the data. The result of the research is that the form of directive utterence in declarative sentences in Japanese drama series (in order of the most) is dantei, suiryou, utagai, and ketsui. Keywords: declarative sentences; directive utterence; pragmatic.